Objek Wisata Air Terjun Tiwu Papa Di Desa Raburia Kecamatan Ende Kabupaten Ende (Dengan Pendekatan Arsitektur Vernakular) - Mochdar, Dian Fitriawati; Wara, Damoses; Kerong, Fabiola T.A. (Program Studi Teknik Sipil dan Program Studi Arsitektur Fakultas Sains & Teknologi Universitas Flores, 2023)
One of the natural tourism objects in Ende Regency which is currently starting to appear and be arranged is the Tiwu Papa Waterfall, as one of the natural tourist objects in Raburia Village, Ende District, Ende Regency, East Nusa Tenggara Province. The Tiwu Papa Waterfall Tourism Object has great potential to be reorganized because of its beautiful place and increasing visits. However, this high potential is still not supported by the availability of main facilities and supporting facilities. The method used is a qualitative and quantitative descriptive analysis method. The concept of the approach is the concept of Vernacular Architecture as a design reference because of the importance of preserving local uniqueness and uniqueness of the area which can be embodied in tourist attraction buildings by considering the local climate, techniques and materials as an effort to maintain the richness of local culture. Design analysis includes site and environmental analysis, actor analysis, spatial scale analysis, form analysis and outdoor space analysis as well as utility analysis. The results obtained from the design of the Tiwu Papa Waterfall Tourism Object refer to the Vernacular Architecture Concept as a design reference, namely by utilizing the land around the waterfall tourist object and to attract the attention of recreational tourists and bathing in the waterfall pool. The facilities built at this tourist attraction consist of main facilities including management buildings, bathing pools, recreational rides, wooden bridges, and supporting facilities including parking, gazebos, as well as bathrooms and changing rooms.